A methodology for modelling organisational governance : building the ‘Good Regulator’ model for organisations through the application of multiple systems methods - Hilton, Jeremy (Cranfield University, 2023)
It is not disputed that organisations require good governance and management to be successful. However, identifying the factors that lead to successful organisational outcomes is not so straightforward. Indeed, enabling an organisation to be resilient to environmental turbulence requires a complete and coherent appreciation of organisational operations and the interdependencies between the organisation and its environment. The purpose of this doctoral thesis is twofold. Firstly, to determine the requirements for a set of systems methods to appropriately model the multidimensional complexity of an organisation. Secondly, to develop a bespoke Reference Model of Governance for a Specific Organisation with multiple systems approaches and a methodology with which to inform a systemic structure for organisational governance and management. By applying the ‘Good Regulator’ model as a foundation, this thesis initially explores the complexity of an organisation and its interaction with its environment to determine the requirements for a set of systems methods. Recent approaches to multi-methodology design and application are reviewed. A set of candidate systems approaches is reviewed. Angyal’s systems framework is used to guide the selection of systems methods to ensure relevant human factors are incorporated. The resulting arrangement is mapped to the requirements set and used to instantiate a Reference Model of Governance for GroundsWell, a research consortium. Drawing on the literature, a tailored approach to validation is developed and successfully applied to the GroundsWell Reference Model of Governance. The primary novel contribution to knowledge is the development of a methodology for the arrangement of multiple systems methods and their application to build a Reference Model of Governance for a Specific Organisation, including validation, for organisational governance and management. Other novel contributions include the layered application of methods to better reflect the hierarchy of purpose within an organisational context and an approach to Validation. In its application, I have successfully demonstrated the instantiated Reference Model of Governance for a Specific Organisation is sufficient to identify the factors that need regulating to ensure desired organisational outcomes and enable the organisation to be resilient to external and internal impacts.
Healy, Matthew - Associate Supervisor
Keywords: Complexity; Complex systems; Systems approach; Systems thinking; Critical systems practice; Organisations; Cybernetics; Multiple perspectives; Hierarchy of purpose